Addressing context dependence in ecology - Catford, Jane A; Wilson, John R U; Pyšek, Petr; Hulme, Philip E; Duncan, Richard P (Trends in ecology & evolution, 2022)
Context dependence is widely invoked to explain disparate results in ecology. It arises when the magnitude or sign of a relationship varies due to the conditions under which it is observed. Such variation, especially when unexplained, can lead to spurious or seemingly contradictory conclusions, which can limit understanding and our ability to transfer findings across studies, space, and time. Using examples from biological invasions, we identify two types of context dependence resulting from four sources: mechanistic context dependence arises from interaction effects; and apparent context dependence can arise from the presence of confounding factors, problems of statistical inference, and methodological differences among studies. Addressing context dependence is a critical challenge in ecology, essential for increased understanding and prediction.
Keywords: experimental design and statistics; ekologie; apparent and mechanistic context dependence; multiple stressors and global environmental change factors; ecological interaction effects; contingency and higher-order interactions; Ecology; invasive alien species